Research progress on animal habitat constructions from the perspective of urban biodiversity improvement - Liu, Zhiruo; Yin, Hao; Wang, Yang; Cheng, Qiushuang; Wang, Zihan (Frontiers in Environmental Science, 2024)
The accelerated urbanization process has caused problems such as habitat loss, isolation, and habitat quality decline, resulting in a sharp reduction in the richness and abundance of urban species. Constructing suitable habitat environmental conditions is the most direct and effective way to protect animals. In urban environment, habitat construction can be achieved by integrating species protection and landscape planning, which is also an important manifestation of biodiversity conservation at the ecosystem level. Understanding how to incorporate animal habitats into city plan and design is critical and urban planners would benefit from a review that holistically describes the steps and methods of animal habitat constructions. We conducted a review to highlight the animal habitats space resources and network structures. We synthesized the findings of research studies in the last 20 years to illuminate the investigation, assessment, planning and management of animal habitats. As habitat degradation and fragmentation in anthropogenic environments, our findings suggest city planners should consider ecological background investigation, habitat suitability assessment, habitat planning strategies and animal habitat management as four key steps of mitigation to alleviate these impacts. This study will provide a useful reference to improve animal survival quality and communication. Through this study, the consolidated research can aid in sustainable development and innovation to promote the ecological function of urban green space and the harmonious coexistence of humans and animals.